2016
DOI: 10.1111/tid.12613
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and outcomes of invasive Candida infections among organ transplant recipients in the United States: results of the Transplant‐Associated Infection Surveillance Network (TRANSNET)

Abstract: Background: Invasive candidiasis (IC) is a common cause of mortality in solid organ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
132
3
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 59 publications
10
132
3
3
Order By: Relevance
“…According to data obtained in this study and from previous studies, C. tropicalis is the third commonest pathogenic Candida species in China, and its prevalence has generally been stable (15–20%; Wang et al, 2012; Liu et al, 2014; Xiao et al, 2015). In addition, some previous studies indicated that invasive infections caused by C. tropicalis have higher mortality compared to those caused by other non- tropicalis Candida species (Montagna et al, 2013; Andes et al, 2016). …”
Section: Discussionmentioning
confidence: 97%
“…According to data obtained in this study and from previous studies, C. tropicalis is the third commonest pathogenic Candida species in China, and its prevalence has generally been stable (15–20%; Wang et al, 2012; Liu et al, 2014; Xiao et al, 2015). In addition, some previous studies indicated that invasive infections caused by C. tropicalis have higher mortality compared to those caused by other non- tropicalis Candida species (Montagna et al, 2013; Andes et al, 2016). …”
Section: Discussionmentioning
confidence: 97%
“…Neutrophils are a critical first line of defense against fungal pathogens, including Candida 2,1418 . In response to planktonic, or non-biofilm C .…”
Section: Introductionmentioning
confidence: 99%
“…Of these, C . glabrata is frequently the most prevalent, particularly in Europe and North America 18,28 . This emerging pathogen poses obstacles to treatment, including increased intrinsic resistance to commonly used antifungals, such as azoles, and the rapid emergence of drug resistance during treatment 4,29 .…”
Section: Introductionmentioning
confidence: 99%
“…(I) Gastrointestinal surgical patients and/or those admitted for necrotizing pancreatitis may constitute a higher risk group that was under-represented in that study (17,18); (II) the study excluded immuno-compromised patients including solid organ transplant or hematopoietic stem cell recipients, which is logical regarding the specificities of fungal infections among that population (19). These immuno-compromised patients are frequently hospitalized in the ICU and represent a challenge for both diagnosis and treatment of fungal infections (20)(21)(22); (III) the lack of use of selective digestive decontamination in the French ICUs may have been balanced with prior exposure to broad spectrum antibiotic therapy. However, it could also explain an incidence of invasive fungal infection lower than that observed in other countries (23); (IV) besides β-Dglucan, the evaluation or the discovery of other biomarkers is warranted to determine, more precisely, which patients would benefit from systemic antifungal therapy to prevent invasive candidiasis, a still unresolved issue (24).…”
Section: Editorialmentioning
confidence: 99%